2017
DOI: 10.1177/0271678x16685106
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal insulin treatment of an experimental model of moderate traumatic brain injury

Abstract: Traumatic brain injury (TBI) results in learning and memory dysfunction. Cognitive deficits result from cellular and metabolic dysfunction after injury, including decreased cerebral glucose uptake and inflammation. This study assessed the ability of intranasal insulin to increase cerebral glucose uptake after injury, reduce lesion volume, improve memory and learning function and reduce inflammation. Adult male rats received a controlled cortical impact (CCI) injury followed by intranasal insulin or saline trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 55 publications
2
60
0
Order By: Relevance
“…Our previous work demonstrated that after a moderate TBI in rats, intranasal insulin administered within 4 h after injury significantly increased glucose uptake in the hippocampus, improved cognitive function, and reduced inflammation (Brabazon et al, 2017). In this study, insulin administered daily for 14 days significantly improved performance in a Morris water maze task as well as improved time to cross a beam during a beam walk task.…”
Section: Insulin Therapysupporting
confidence: 55%
“…Our previous work demonstrated that after a moderate TBI in rats, intranasal insulin administered within 4 h after injury significantly increased glucose uptake in the hippocampus, improved cognitive function, and reduced inflammation (Brabazon et al, 2017). In this study, insulin administered daily for 14 days significantly improved performance in a Morris water maze task as well as improved time to cross a beam during a beam walk task.…”
Section: Insulin Therapysupporting
confidence: 55%
“…[ 23 ] Our lab has shown a significant improvement in memory function after moderate brain injury with intranasal insulin treatment. [ 24 ] Interestingly, this improvement in memory function was correlated with a significant reduction in microglial staining in the brain after intranasal insulin treatment, similar to that observed by Chen et al[ 23 ]…”
Section: Introductionmentioning
(Expert classified)
“…In fact, previous studies have reported poorer performance on the Morris water maze tests as early as 2 weeks after TBI. [36][37][38] We speculated that persistent cortex, hippocampus, and corpus callosum abnormalities revealed by the DKI parameter changes would cause disruption of the brain cognitive network, thus leading to cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%